Analysis of substitution times in soccer - Silva, R. M.; Swartz, T. B. (Journal of Quantitative Analysis in Sports, 2016)
This paper considers the problem of determining optimal substitution times in soccer. We review the substitution rule proposed by Myers (Myers, B. R. 2012. "A Proposed Decision Rule for the Timing of Soccer Substitutions." Journal of Quantitative Analysis in Sports 8: Article 9.) and provide a discussion of the results. An alternative analysis is then presented that is based on Bayesian logistic regression. We find that with evenly matched teams, there is a goal scoring advantage to the trailing team during the second half of a match. In addition, we provide a different perspective with respect to the substitution guidelines advocated by Myers (Myers, B. R. 2012. "A Proposed Decision Rule for the Timing of Soccer Substitutions." Journal of Quantitative Analysis in Sports 8: Article 9.). Specifically, we observe that there is no discernible time during the second half when there is a benefit due to substitution.